Proposta de um plano de manutenção para um edifício de alto padrão de Curitiba - Costa, Gabriela Eleticia Gonçalves da (2024)
Building maintenance is essential to ensure the safety, functionality, and longevity of buildings. It plays a crucial role in preventing structural problems, avoiding emergency repairs, and high long-term costs. Additionally, regular maintenance ensures that critical systems are always in compliance with safety standards, minimizing the risk of accidents. An efficient maintenance program also contributes to the property’s value in the real estate market, preserving its worth. Thus, this paper conducted a bibliographic research on the subject and a case study in a high-end building located in the city of Curitiba, with the aim of understanding the main maintenance demands. After analyzing the data, it was possible to observe which systems demand the most maintenance attention in a building of this size. Based on this analysis, a building maintenance plan model was developed for a similar residential building that is under construction by the same construction company.